PENERAPAN CRITICAL REVIEW ARTIKEL PEMBELAJARAN IPA UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA DALAM MENYUSUN PROPOSAL SKRIPSI - Parmin, Parmin (PHENOMENON, 2014)
ABSTRACTThe aims of this research is to improve studentsâ ability in developinga proposal thesis by applying critical review of scientific articles comefrom journals. The research is designed by class action research. The resultsshowed 63% of students thesis proposals on Research Methodology coursescored above 80. Based on the results obtained it can be concluded that theapplication has been critical review or critical study of scientific articles canenhance studentsâ ability in preparing research proposals.Keywords: critical review, scientific article, journal and thesisproposal